Mott-Hubbard versus charge-transfer behavior in LaSrMnO 4 studied via optical conductivity - Gössling, Alexander; Haverkort, Maurits W. (Physical review. B, Condensed matter and materials physics, 2008)
Using spectroscopic ellipsometry, we study the optical conductivity σ(ω) of insulating LaSrMnO 4 in the energy range of 0.75-5.8eV from 15to330K. The layered structure gives rise to a pronounced anisotropy. A multipeak structure is observed in σa1(ω) (∼2, 3.5, 4.5, 4.9, and 5.5eV), while only one peak is present at 5.6eV in σc1(ω). We employ a local multiplet calculation and obtain (i) an excellent description of the optical data, (ii) a detailed peak assignment in terms of the multiplet splitting of Mott-Hubbard and charge-transfer absorption bands, and (iii) effective parameters of the electronic structure, e.g., the on-site Coulomb repulsion Ueff=2.2eV, the in-plane charge-transfer energy Δa=4.5eV, and the crystal-field parameters for the d4 configuration (10Dq=1.2eV, Δeg=1.4eV, and Δt2g=0.2eV). The spectral weight of the lowest absorption feature (at 1-2eV) changes by a factor of 2 as a function of temperature, which can be attributed to the change of the nearest-neighbor spin-spin correlation function across the Néel temperature TN=133K. Interpreting LaSrMnO4 effectively as a Mott-Hubbard insulator naturally explains this strong temperature dependence, the relative weight of the different absorption peaks, and the pronounced anisotropy. By means of transmittance measurements, we determine the onset of the optical gap Δaopt=0.4-0.45eV at 15K and 0.1-0.2eV at 300K. Our data show that the crystal-field splitting is too large to explain the anomalous temperature dependence of the c-axis lattice parameter by thermal occupation of excited crystal-field levels. Alternatively, we propose that a thermal population of the upper Hubbard band gives rise to the shrinkage of the c-axis lattice parameter.